Upaya Pemberdayaan Masyarakat Dalam Pengelolaan Konservasi Lingkungan Yang Hidup di RW 11 Kelurahan Pengasinan Kecamatan Rawa Lumbu Kota Bekasi - Refangga, Bagus Hery; Ismail, Randi; Amin, Muhammad Luqman Arif; Sasono, Azhar Fauzi; Damanik, Vico Andreas; Ramadhan, Muhammad Dimas; Ismail, Virdan Yunior; Asworo, Hammam Raihan; Budiman, Arief; Rukmayadi, Dede (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
This research aims to examine and implement community empowerment efforts in managing environmental conservation in Pengasinan Village, Rawa Lumbu District, Bekasi City. The background to this research is the importance of greenery and sports facilities in the community environment. This is caused by a lack of public awareness regarding the importance of environmental management and public health. Through a participatory approach, the Community Service Program (KKN) is implemented to increase community understanding and involvement in environmental conservation efforts. The method used in this research is a qualitative method with data collection techniques through observation, interviews and focus group discussions (FGD). Data were analyzed using a descriptive approach to understand social and ecological dynamics in the Pengasinan Village area, Rawa Lumbu District, Bekasi City. The empowerment program includes counseling, waste management training, development of vertical gardens, and mutual cooperation activities to clean the environment. The research results show that there are three main activities, namely the Greening Program, Reading Park Program, and Sports Facilities which are well implemented and provide various benefits for the community. This research concludes that community empowerment through the KKN program is effective in increasing community participation and awareness of the importance of environmental conservation. The recommendation from this research is the need for continued support from the government and related institutions to maintain program sustainability and expand the scope of activities to other areas in need.